A case of hidradenitis suppurativa linked to trisomy 1q. (19th September 2019) - Skroza, N.; Mambrin, A.; Tolino, E.; Bernardini, N.; Proietti, I.; Anzalone, A.; Marchesiello, A.; Porta, N.; Petrozza, V.; Potenza, C.
Abstract: Hidradenitis suppurativa (HS) is a chronic relapsing disorder of the apocrine gland affecting mainly areas subjected to friction (e.g. the axillae, groin, perineum and medial aspects of the thighs). This condition can be linked to different comorbidities: autoimmune and inflammatory disease, hormone‐related disorders, obesity and the metabolic syndrome, as well as rare syndromes such as Bazex–Dupré–Christol, Down's, KID, PAPASH, PASS, PASH, and SAPHO syndromes, or Dowling–Degos disease. We report a case of severe HS in a patient with Trisomy 1q;13, a very rare cytogenetic anomaly characterized by severe anomalies including dysmorphisms, multiple congenital malformations, heart defects and intellectual disability.